Evaluation of frozen Umbrella‐stage Artemia as first animal live food for Litopenaeus vannamei (Boone) larvae. (13th January 2014) - Cobo, María de Lourdes; Wouters, Roeland; Wille, Mathieu; Sonnenholzner, Stanislaus; Sorgeloos, Patrick
Abstract An alternative larval shrimp feeding regime, in which umbrella‐stage Artemia were constituting the first zooplankton source was evaluated in the culture of Litopenaeus vannamei. In a preliminary experiment, umbrella‐stage Artemia were fed to larvae from zoea 2 (Z2) to mysis 2 (M2) stages to identify the larval stage at which raptorial feeding starts and to determine daily feeding rates. The following experiment evaluated the performance of two feeding regimen that differed during the late zoea/early mysis stages: a control treatment with frozen Artemia nauplii (FAN), and a treatment with frozen umbrella‐stage Artemia (FUA). The ingestion rate of umbrella‐stage Artemia increased from nine umbrella per larvae day−1 at Z2 stage to 21 umbrella per larvae day−1 at M2. A steep increase in ingestion and dry weight from Z3 to M2 suggests a shift to a raptorial feeding mode at the M1 stage. Treatment FUA exhibited a significantly higher larval stage index (P < 0.05) during the period that zoea larvae metamorphosed to the mysis stage, and a higher final biomass, compared with treatment FAN. Based on these results and on practical considerations, a feeding regime starting with umbrella‐stage Artemia from Z2 sub‐stage can be recommended for L. vannamei larvae rearing.